Cultivating Islamic Ideology: Print Islam in Post-Independence Indonesia (A Preliminary Study) - Muzakki, Akh. (Studia Islamika, 2007)
This article examines the development of Islamic print publication in post-independence Indonesia, Particular attention will be given to the trends prevalent among Islamic publishing houses, both in terms of agency and their products, and to Islamic print publication's role in the cultivation and dissemination of certain Islamic ideologies, I will begin with an analyses of the development of Islamic print and non-print publication, Central to this analysis is the delineation of the strength of Islamic print publication compared to that of non-print efforts.DOI: 10.15408/sdi.v14i3.543